2015
DOI: 10.1242/jcs.170258
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifiers reduce inflammation and modulate macrophage phenotype during endotoxemia-induced acute lung injury

Abstract: Acute lung injury (ALI) during sepsis is characterized by bilateral alveolar infiltrates, lung edema, and respiratory failure. Here, we examined the efficacy of DNA methyl transferase (DNMT) inhibitor Aza (5-Aza 2-deoxycytidine), histone deacetylase (HDAC) inhibitor TSA (Trichostatin A), and combination therapy (Aza+TSA) in protection of ALI. In LPS-induced mouse ALI, post-treatment with a single dose of Aza+TSA showed a substantial attenuation of adverse lung histopathological changes, and inflammations. Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 56 publications
(79 reference statements)
3
86
0
1
Order By: Relevance
“…Inhibition of histone deacetylases (HDACs) regulates the acetylation status of different genes associated with inflammation [5,83] or other diseases, such as cancer [84], CVDs [85], and metabolic homeostasis [86]. In recent years, HDAC inhibitors have demonstrated great potential in serving as a therapeutic treatment for the suppression of inflammation in macrophages.…”
Section: Epigenetic Modifiers and Macrophage Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of histone deacetylases (HDACs) regulates the acetylation status of different genes associated with inflammation [5,83] or other diseases, such as cancer [84], CVDs [85], and metabolic homeostasis [86]. In recent years, HDAC inhibitors have demonstrated great potential in serving as a therapeutic treatment for the suppression of inflammation in macrophages.…”
Section: Epigenetic Modifiers and Macrophage Polarizationmentioning
confidence: 99%
“…Recently, it was shown that 5-Aza 2-deoxycytidine (Aza), a DNMTi and TSA, a total inhibitor for HDACs, have the potential to treat inflammation. The study demonstrated that the combination of Aza+TSA not only decreased the expression of M1 macrophages, but also increased M2 macrophage expression in LPS-induced primary mouse bone marrow-derived macrophages (BMDMs) [13]. …”
Section: Combination Of Epigenetic Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of combinatorial administration of Aza+TSA after the onset of acute lung injury (ALI) has been found to significantly attenuate lung vascular hyper permeability and inflammatory lung injury. Moreover, the combinatorial treatment with Aza+TSA reduces inflammation and promotes anti-inflammatory M2 macrophages during ALI [135, 136]. These two studies clearly demonstrated that epigenetic modifiers have a therapeutic potential for patients with sepsis-induced vascular injury and inflammation.…”
Section: Clinical Relevance Of Epigenetic Modifiersmentioning
confidence: 99%
“…It will be of great interest to learn, if macrophages stimulated by other stress-signals will respond in a similar fashion to these novel JMJD3 and UTX inhibitors. Further promising support for targeting transcriptional and epigenetic regulation comes from a study using the DNA methyl transferase (DNMT) inhibitor 5-Aza 2-deoxycytidine (Aza) and the HDAC inhibitor Trichostatin A (TSA) to treat murine LPS-induced acute lung injury [61]. Combinatorial treatment with Aza + TSA reduced inflammation and promoted an anti-inflammatory macrophage program.…”
Section: Novel Opportunities Targeting Macrophagesmentioning
confidence: 99%